Regular Industrial Processing of Bovine Milk Impacts the Integrity and Molecular Composition of Extracellular Vesicles. Issue 6 (25th March 2021) - Kleinjan, Marije; van Herwijnen, Martijn JC; Libregts, Sten FWM; van Neerven, RJ Joost; Feitsma, Anouk L; Wauben, Marca HM
Abstract: Background: Bovine milk contains extracellular vesicles (EVs), which act as mediators of intercellular communication by regulating the recipients' cellular processes via their selectively incorporated bioactive molecules. Because some of these EV components are evolutionarily conserved, EVs present in commercial milk might have the potential to regulate cellular processes in human consumers. Objectives: Because commercial milk is subjected to industrial processing, we investigated its effect on the number and integrity of isolated milk EVs and their bioactive components. For this, we compared EVs isolated from raw bovine milk with EVs isolated from different types of commercial milk, including pasteurized milk, either homogenized or not, and ultra heat treated (UHT) milk. Methods: EVs were separated from other milk components by differential centrifugation, followed by density gradient ultracentrifugation. EVs from different milk types were compared by single-particle high-resolution fluorescence-based flow cytometry to determine EV numbers, Cryo-electron microscopy to visualize EV integrity and morphology, western blot analysis to investigate EV-associated protein cargo, and RNA analysis to assess total small RNA concentration and milk-EV-specific microRNA expression. Results: In UHT milk, we could not detect intact EVs. Interestingly, although pasteurization (irrespective of homogenization) did not affect mean ± SD EV numbers (3.4 × 10 8 ± 1.2 × 10 8 –2.8 × 10 8 ± 0.3 × 10 7 compared with 3.1 × 10 8 ± 1.2 × 10 8 in raw milk), it affected EV integrity and appearance, altered their protein signature, and resulted in a loss of milk-EV-associated RNAs (from 40.2 ± 3.4 ng/μL in raw milk to 17.7 ± 5.4–23.3 ± 10.0 mg/μL in processed milk, P < 0.05). Conclusions: Commercial milk, that has been heated by either pasteurization or UHT, contains fewer or no intact EVs, respectively. Although most EVs seemed resistant to pasteurization based on particle numbers, their integrity was affected and their molecular composition was altered. Thus, the possible transfer of bioactive components via bovine milk EVs to human consumers is likely diminished or altered in heat-treated commercial milk.